A brief review on recent graphene oxide-based material nanocomposites: synthesis and applications - Hashim, Norhayati; Muda, Zuhailimuna; Hussein, Mohd Zobir; Md Isa, Illyas; Mohamed, Azmi; Kamari, Azlan; Abu Bakar, Suriani; Mamat, Mazidah; Mohamad Jaafar, Adila (University of Mohammed Premier Oujda, 2016)
In a past few years, more focus has been given to graphene, especially for its facile synthesis, novel hybrids materials and applications. Recently, researchers' attention has also focused on graphene oxide (GO) and reduced graphene oxide (rGO) nanocomposites, which lead to the development of various applications. Their superb and impressive characteristic makes them suitable candidates to be hybridized with polymer, metal oxide, and biomaterials. In this brief review, we will run through the accomplishments of effective approaches for synthesizing graphene oxide-based material nanocomposites together with their recently developed applications.